2018
DOI: 10.15520/ijcrr/2018/9/03/460
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Compensation and Work Environment on Employee Performance with Employee Job Satisfaction as an Intervening Variable

Abstract: An employee who has a high performance and better able to support the achievement of the goals and objectives set by the company. Employees can work well if you have a high performance that can produce good work anyway. With the high- performance that employees, is expected to achieve organizational goals. This study examines the effect of compensation and work environment on employee performance with job satisfaction to be intervening variable. Data on compensation, work environment, job satisfaction, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 0 publications
5
13
0
5
Order By: Relevance
“…The results of compensation research on employee performance also support the results of previous studies conducted by Sopiah (2013) Suryadharma et al (2016), Juliarti et al (2018) the conclusion of his research results shows that compensation has a positive and significant effect on employee performance. However, it is different from the results of the study of Shahab & Nisa (2014) and Rachmawati & Mauludin (2018) the research results conclude that incentives do not significantly influence performance.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…The results of compensation research on employee performance also support the results of previous studies conducted by Sopiah (2013) Suryadharma et al (2016), Juliarti et al (2018) the conclusion of his research results shows that compensation has a positive and significant effect on employee performance. However, it is different from the results of the study of Shahab & Nisa (2014) and Rachmawati & Mauludin (2018) the research results conclude that incentives do not significantly influence performance.…”
Section: Discussionsupporting
confidence: 86%
“…The results of the job satisfaction research on employee performance also support the results of previous studies conducted by : Yusuf et al (2012), Sopiah (2013), Gayathiri et al (2013), Mardiono & Supriyatin (2014), Shahab & Nisa (2014), Umar (2014), Arifin (2015), Suryadharma et al (2016), and Juliarti et al (2018) in the conclusion of the results of his study showed that job satisfaction has a positive and significant effect on employee performance. PT.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations